Structural optimization and material selection in pediatric upper limb myoelectric prosthesis...XXI Brazilian Congress of Biomechanics (CBB), April 30-03 May, 2025, Petrolina, Brazil. - Ferreira Ganga, Thabata Alcantara; Rorato, Eduardo Keller; de Oliveira Basso, Beatriz Fernanda; Lima, Mário Oliveira; Kunkel, Maria Elizete (Brazilian Journal of Motor Behavior)
Background: Upper limb amputations in children present significant challenges, especially when the residual limb is too short to allow effective use of body-powered prostheses. In such cases, the force required to operate mechanical systems is excessive, leading to discomfort and limited functionality. Myoelectric prostheses, which use muscle signals to control movement, provide an alternative that eliminates the need for physical effort. However, these devices are often expensive, heavy, and not designed to accommodate pediatric growth, leading to low adoption rates. The lack of accessible myoelectric options highlights the need for a lightweight, adaptable, and costeffective solution. This study is part of a broader effort to develop an innovative pediatric myoelectric prosthesis using additive manufacturing thermoplastics. 3D printing technology enables customizable designs, reducing weight and allowing continuous adjustments as the child grows. This research focuses on optimizing the prosthesis structure and selecting appropriate materials to ensure durability and mechanical efficiency. Objective: This study aims to enhance the structural design of a pediatric myoelectric prosthesis and identify suitable materials for additive manufacturing that offer strength, low weight, and flexibility compatible with pediatric biomechanics. Material and Methods: Finite element analysis (FEA) of the open-source Limbitless Arm model was conducted using Fusion 360 to identify stress concentration points and structural weaknesses. Reinforcements were implemented while maintaining a lightweight profile. A revised version of the model was 3D printed using polylactic acid (PLA) to evaluate fit, articulation, and assembly feasibility prior to integrating electronic components. A systematic material selection process was conducted to evaluate multiple thermoplastics compatible with additive manufacturing (melting temperature < 300°C). The following materials were analyzed: PLA, acrylonitrile butadiene styrene (ABS), polyethylene terephthalate glycol (PETG), acrylonitrile styrene acrylate (ASA), polypropylene (PP), polyamide 6 (PA6), and their carbon fiber-reinforced variants (PLA CF, PETG CF, PA6 CF). Materials were compared based on stiffness-to-weight ratio, rigidity, flexibility, and cost. The three most promising candidates were highlighted in the results section. Results: The PLA prototype validated the optimized structural design, identifying further refinements needed in joint articulation and stress distribution. From the evaluated options, PA6 CF showed the highest stiffness-to-weight ratio (Me = 2.89) but limited flexibility (Me = 0.083) and high cost (R$ 900.00/kg). PETG CF provided a balanced compromise between stiffness (Me = 2.38) and flexibility (Me = 0.100) at a lower cost (R$ 300.00/kg). PLA CF offered the greatest flexibility (Me = 0.167) but had the lowest stiffness among the selected materials (Me = 2.11), which affected structural performance. Conclusions: No single material fully satisfied all mechanical performance criteria, indicating the need for further material adjustments. Exploring composite structures, such as sandwich-structured configurations, may improve the balance between rigidity and flexibility in future prosthesis iterations. The combination of FEA-based structural optimization and material selection established a strong foundation for the next development phase. Future work will focus on fabricating functional prototypes using selected materials, followed by extensive mechanical testing. Additionally, a secondary material selection phase will compare the prosthesis’s mechanical properties with human tissues to improve comfort and usability.